Clinical features and surgical treatment of mediastinal masses in children: a retrospective study of 51 cases - Shang, Xianhui; Liu, Yuanmei; Luo, Zhen; Li, Yingbo; Zhou, Guangxu; Tan, Hongyang; Mao, Kaiyi (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the clinical features, imaging manifestations, pathological types, and surgical strategies of mediastinal masses in children with this condition, aiming to enhance early diagnosis and perioperative management.MethodsClinical data of children diagnosed with mediastinal masses and treated at the Affiliated Hospital of Zunyi Medical University between January 2019 and August 2024 were retrospectively reviewed. Key variables analyzed included demographic characteristics, clinical presentation, imaging findings, surgical procedures, intraoperative management, pathological results, and follow-up outcomes. Risk stratification and intraoperative safety strategies were assessed through representative complex case analyses.ResultsA total of 51 children were enrolled, comprising 29 males and 22 females, with a median age of 5.0 years. Primary clinical presentations included shortness of breath upon exertion (54.9%) and cough (49.0%), while 5 children were asymptomatic. All diagnoses were confirmed by computed tomography (CT), with lesions predominantly located in the middle and posterior mediastinum. Ganglioneuroma, bronchogenic cyst, and schwannoma were the most common types. Benign lesions accounted for 84.3%, whereas 8 cases were malignant. Thoracoscopic surgery was performed in 45 children and open thoracotomy in 6. Intraoperatively, iodine solution was applied to cystic lesions in 16 cases, and sclerosing agent injections were administered to 4 lymphangioma cases. Postoperatively, 10 children with malignant tumors required subsequent oncological treatment. One child encountered mechanical ventilation failure during anesthetic induction, which was resolved by transitioning to a prone position. In bronchogenic cysts, preemptive decompression effectively prevented complications such as bronchial obstruction.ConclusionMediastinal masses in children are predominantly benign, frequently presenting with nonspecific respiratory symptoms, and CT remains the diagnostic modality of choice. Surgical resection was the primary treatment. Individualized intraoperative management based on lesion type, appropriate patient positioning, and decompression procedures can significantly reduce complication risks. Preoperative airway compression assessment and collaboration with anesthesia teams to establish emergency ventilation protocols are essential to ensuring perioperative safety in children.